FENOMENA SAMPURAGA PERSFEKTIF MASYARAKAT DESA SIRAMBAS KABUPATEN MANDAILING NATAL - Indra Harahap; sholahuddin Ashani; Tuti Alawiyah (UIN Sumatera Utara Medan, 2021)
Every religious teaching and any dogma to do good or to be devoted to both parents is a teaching obligation for every child, How many incidents of children disobeying their parents, God quickly cursed this despicable act. The Sampuraga phenomenon is found in Sirambas Village which tells the story of a child who is disobedient to his mother. His treatment of not acknowledging his biological mother and ordering the ulubalang to drag and expel his pregnant mother until her clothes tore into a problem point in this study. The formulation of the problem in this study is the view of the people of Sirambas Village on the Sampuraga phenomenon. And the effectiveness of the Sampuraga phenomenon in realizing the noble character of the Millennial Generation. This problem is studied through field research methods with a phenomenological approach. And use interaction theory. The data collection techniques in this study using interview and documentation techniques. The results of this study found that some of the people of Sirambas Village, Panyabungan Barat District, believed that the phenomenon of the hot springs of Sampuraga was the incarnation of Sampuraga who was disobedient to his mother. this is illustrated when Sampuraga does not recognize his biological mother. Even ordered the ulubalang to expel the mother.some people think the story is just a folk tale. The people of Sirambas Village agree that there is a positive influence from the Sampuraga phenomenon to realize the noble character of children. There are moral and religious messages contained in the Sampuraga phenomenon that can be used as learning media in realizing noble character in children.